Web-mapping Potential and its Use for Mapping of Land Value Parameters - Bogdanets, V. (Land Management, Cadastre and Land Monitoring, 2020)
Web mapping is a powerful tool for visualizing geospatial information about those properties of land resources that determine the parameters of their value assessment, as well as the influence of natural and anthropogenic factors on land valuation. MapServer rendering of land valuation parameters can be solved with MapServer services. Another problem with web mapping of land valuation parameters is the question of the qualitative and quantitative characteristics of the data that will be used to create the mapping materials. Currently, there are well-developed web-mapping technologies in the world that allow you to visualize the indicators and parameters of land and their condition by means of geo-mapping mapping using a variety of techniques for displaying them to the user. Currently, the main features are Map Server open source and ArcGIS Server commercial platform. Expanding the web mapping are the priority of expanding the palette of imaging tools and improving ways to display complex attribute, including simultaneous, information in combination with mapping images, while developing client-server technologies to implement OGC tasks using web 3.0 and web 4.0.Keywords: web mapping, land resources, land valuation parameters, land quality accounting.